Criticism and politeness strategies in academic review discourse: a contrastive (English-Italian) corpus-based analysis - Diani, Giuliana (Kalbotyra, 2017)
Drawing on a corpus-based approach, this paper explores the mitigation strategies used to soften criticism in English and Italian book review articles in the disciplinary field of linguistics. Most corpus-based analyses on academic criticism have focused on the use and function of politeness strategies in English academic review genres, mainly book reviews. Recently, an increasing number of studies on academic book reviews have examined the issue from a cross-cultural perspective. This study attempts to contribute to the area of cross-cultural research on reviewing practices by exploring how criticisms are managed in a somewhat neglected review genre in academic discourse studies – the book review article. Criticisms will be identified on the basis of their lexico-grammatical features and further categorized into “direct” and “mitigated” (Itakura & Tsui 2011, 1369). The mitigation strategies identified in both language corpora mainly involve the use of sequences of speech acts such as praise-criticism, criticism-praise, criticism-suggestion, praise-suggestion, and hedging. However, their distributions reveal differences in the two languages. While praise is prominently used in both English and Italian book review articles, Italian-speaking linguistics reviewers employ a lower proportion of hedges than their English-speaking colleagues and are more likely to opt for suggestions as a form of indirect criticism. The results demonstrate that linguistics reviewers writing in English and Italian deploy a considerable range of linguistic devices when expressing mitigated criticism of peers. Their use and distribution are discussed in relation to national/cultural writing conventions, but also differences between “large” and “small” disciplinary cultures (Holliday 1999). Some implications for EAP learners and practitioners are also considered.
Keywords: corpus-based analysis; cross-cultural analysis (English and Italian); book review articles; academic criticism; politeness strategies